Synthesis of lignin based composites of TiO2 for potential application as radical scavengers in sunscreen formulation - Mohamad Nasir, Mohamad Ibrahim; Anwar, Iqbal; Chai, Chuan Shen; Showkat, Ahmad Bhawani; Farook, Adam (BioMed Central, 2019)
Titanium dioxide (TiO2) is added in sunscreens due to its ability to absorb ultraviolet (UV) light. However, upon irradiation of UV light, reactive oxygen species particularly hydroxyl radical which can damage human skin will be generated. In this study, lignin/TiO2 composites were employed to quench the hydroxyl radicals generated by the TiO2. The lignin was extracted from oil palm empty fruit bunch (OPEFB) via kraft and soda pulping processes. The kraft lignin composite was labelled as KL/TiO2 whereas the soda lignin composite was labelled as SL/TiO2. The lignins and the composites were characterized by FTIR, UV spectroscopy, 13C NMR, SEM, EDX, and XRD. The relative hydroxyl radical production of composites and TiO2 were compared through photo-oxidation of coumarin to 7-hydroxycoumarin as a test medium. The efect of types and amounts of lignin used were studied. The KL/TiO2 composite showed the least radical production due to higher phenolic hydroxyl content of kraft lignin. The activity of the hydroxyl radicals will be quenched when it abstract hydrogen atoms from the phenolic hydroxyl groups.